Impedance cardiography parameters reflecting left ventricular function are markers of pulmonary arterial hypertension - Wentao, Yang; Yumiao, Wang; Luanluan, Yang; Xin, Li; Xiaopei, Cui (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPre-capillary pulmonary hypertension (PH) is characterized by pulmonary vascular remodeling and right heart failure. We aim to identify impedance cardiography (ICG) parameters with potential for pre-capillary PH screening and prognostic prediction.MethodsA discovery cohort consisting of 26 patients with pulmonary arterial hypertension (PAH) and 20 healthy volunteers was enrolled from August 2018 to March 2019. Another 100 patients who had undergone right heart catheterization (RHC) due to suspected PAH were enrolled from April 2019 to August 2020 as the validation cohort. In total, 62 patients with pre-capillary PH in the discovery and validation cohorts were followed up for 41 months. The relationships between ICG parameters and pre-capillary PH screening and prognostic prediction were studied.ResultsPatients with pre-capillary PH exhibited lower left ventricular stroke work (LSW) and left ventricular stroke work index (LSWI) values compared to the healthy controls, which was further proved in the validation cohort [51.5 (41.8–67.2) vs. 69.7 (68.1–72.3) g·m/beat, p = 0.014 for LSW; 30.9 (26.5–40.9) vs. 41.7 (40.8–43.8) g·m/beat/m2, p = 0.026 for LSWI]. Patients with low risk status at baseline exhibited much higher LSW [57.1 (45.8, 73.1) vs. 45.8 (35.1, 57.4) g·m/beat, p = 0.002] and LSWI [35.1 (28.4, 43.7) vs. 27.2 (20.4, 36.3) g·m/beat/m2, p < 0.001] than those at intermediate/high risk. The cut-off points that predicted PAH low risk status were 57.85 g·m/beat (sensitivity 59% and specificity 63%) for LSW and 36.75 g·m/beat/m2 (sensitivity 61% and specificity 79%) for LSWI. During follow-up, the hazard ratio (HR) for a clinical worsening event in the LSW < 58 g·m/beat group was 8.80 [95% confidence interval (CI): 3.16–24.54; p = 0.0001]. This was the same in the LSWI < 37 g·m/beat/m2 group (HR = 7.36, 95% CI: 2.65–20.44; p = 0.0001).ConclusionLSW and LSWI detected by ICG are useful in pre-capillary PH screening and valuable as long-term predictors of clinical worsening in pre-capillary PH treatment.